Managerial and financial barriers to the green transition - Ralph de Haas; Ralf Martin; Mirabelle Muûls; Helena Schweiger (National Bank of Belgium, 2023)
Using data on 10,769 firms across 22 emerging markets, we show that both credit constraints and weak green management hold back corporate investment in green technologies embodied in new machinery, equipment and vehicles. In contrast, investment in measures to explicitly reduce emissions and other pollution, is mainly determined by the quality of a firm's green management and less so by binding credit constraints. In addition, data from the European Pollutant Release and Transfer Register reveal the climate impact of these organizational constraints. In areas where more firms are credit constrained and weakly managed, industrial facilities systematically emit more CO2 and other greenhouse gases. A counterfactual analysis shows that credit constraints and weak management have respectively kept CO2 emissions 4.8% and 2.2% above the levels that would have prevailed without such constraints. This is further corroborated by our finding that in localities where banks had to deleverage more due to the Global Financial Crisis, carbon emissions by industrial facilities remained 5.7% higher a decade later.
Keywords: D22; L23; G32; L20; Q52; Q53; 330; Green management; credit constraints; CO2 emissions; energy efficiency